2018
DOI: 10.3390/environments5060064
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Urban Sound Environment in Greece: A Guide Based on Selected Case Studies of Strategic Noise Maps (SNM) and Noise Action Plans (NAP) in Medium and Large Urban Areas

Abstract: Within the frame of European directive 2002/49 for Strategic Noise Mapping and the relevant environmental Noise Action Plans, which included preparation for the management of environmental noise and the rehabilitation of the sound environment, Greece had the opportunity to develop an innovative and comprehensive methodology to analyze the sound environments of several urban and semi-urban residential neighborhoods in the large and medium-size cities of the country e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…The results describe how sonic comfort by the residents of a neighborhood is perceived and assessed. They describe the place of noise in all sources of the environment and, above all, allow a certain number of recommendations to be made for the management of the soundscape in relation to the recommendations of the Noise Action and Soundscape Plan [15].…”
Section: Acoustic Comfort and Sonic Identities Assessment Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The results describe how sonic comfort by the residents of a neighborhood is perceived and assessed. They describe the place of noise in all sources of the environment and, above all, allow a certain number of recommendations to be made for the management of the soundscape in relation to the recommendations of the Noise Action and Soundscape Plan [15].…”
Section: Acoustic Comfort and Sonic Identities Assessment Methodologymentioning
confidence: 99%
“…In 2013, according to the legislation and European Directive 2002/49, a full Strategic Noise Map (SNM) and Noise Action Plan (NAP) were completed. Given the efficiency of such an action plan [12,13], we developed during several environmental studies a specific methodology in order to cross-analyze the acoustic data with the perception of the soundscapes [14,15] and draw an global action plan for noise exposure and soundscape management. It has been applied to the subarea of Alikarnassos and the main results are presented in the following paragraphs.…”
Section: The International Airport Of Heraklionmentioning
confidence: 99%
“…In the example above, the comparison of the two SNM presents the impact of the environmental noise generated by the air traffic and especially its influence on the whole neighborhood studied here. This tool intelligently reinforces the scenario for moving the airport to a less developed area [9,10]. Therefore by providing a common framework, the EU Member States have introduced intelligent tools that allow the simple translation and assessment of a large number of sources of environmental noise.…”
Section: Smart Tools For Environmental Noise Exposurementioning
confidence: 99%
“…The NAP proposed the installation of five one-level roundabouts in order to streamline traffic, reduce traffic speeds, and thus reduce the noise emitted by vehicles. In the late 2018, four roundabouts are already constructed, and local studies and monitoring programs have already shown the positive impact of these mitigation measures concerning the environmental noise [9] (Figure 10).…”
Section: Smart Tools For City Developmentmentioning
confidence: 99%
See 1 more Smart Citation